ANGIOTENSIN II INDUCED SALT-SENSITIVE HYPERTENSION ASSOCIATED WITH INVERSE CIRCADIAN PATTERN IN RENAL GENERATION OF TUMOR NECROSIS FACTOR ALPHA AND ANGIOTENSINOGEN IN MICE. (April 2021) - Majid, Dewan S A; Navar, L. Gabriel; Castillo, Alexander; Khan, Nadia; Shindler, Isabella
Abstract : Objective: Blood pressure (BP) in humans normally follows a circadian dipping pattern with a decline from day (active) to a night (inactive) period. Such dipping pattern is altered to a non-dipping pattern in salt-sensitive hypertension (SSH), the pathophysiological mechanism of which is not yet clearly understood. Angiotensin II (AngII) induced SSH associated with increased intrarenal AGT generation, which can be suppressed by tumor necrosis factor-alpha (TNFa) formation. We examined the hypothesis that AngII-induced TNF and AGT generation follows an inverse circadian pattern with a decrease in TNF during inactive period that facilitates increased AGT generation leads to non-dipping pattern in SSH. Design and method: Experiments were performed in mice (C57BL6 strain) chronically treated with or without AngII (25 ng/min; osmotic mini-pump) and high salt (HS; 4% NaCl) containing diets for 4 weeks. BP was measured at day and night periods by tail-cuff method. Circadian rhythm in urinary parameters in these nocturnal animals was assessed by 12 hour urine collections using metabolic cages during the active period (7PM to 7AM) and the inactive period (7 AM to 7 PM). Results: In untreated rats (n = 6), mean BP showed dipping pattern (90 ± 3 to 78 ± 2 mmHg from active to inactive period) AngII + HS treatment (n = 6) induced a non-dipping pattern of SSH (109 ± 2 to 106 ± 3 mmHg from active to inactive period). In untreated mice, urinary excretion of TNFa (uTNFa) was higher (0.5 ± 0.2 vs 0.13 ± 0.08 pg/hour) but urinary excretion of AGT (uAGT) was lower (0.28 ± 0.18 vs 0.46 ± 0.14 ng/hour) during the active period compared to that during the inactive period. This inverse relationship between uTNFa and uAGT was exaggerated in AngII+HS treated mice. There were marked increases in uTNFa during active periods (44.6 ± 14.6 pg/hour) which were less during inactive periods (12.1 ± 4.7 pg/hour). Interestingly, uAGT increment was lower during active periods (1.42 ± 0.97 ng/hour) than that in inactive periods (3.98 ± 1.67 ng/hour). Conclusions: TNFa generation suppresses intra-renal AGT formation during active periods but this phenomenon is inversed during inactive periods. The increase in AGT during the inactive period may facilitates a non-dipping BP pattern in SSH.